Patient preferences for endpoints in fecal incontinence treatment studies. Issue 5 (8th March 2017) - Heymen, S.; Palsson, O.; Simren, M.; Whitehead, W. E.
Abstract: Background: Randomized controlled trials of treatments for fecal incontinence (FI) are difficult to compare because case definitions and study endpoints vary. Our aims were to assess patient perspectives on the case definition for FI and how treatment success should be measured. Methods: In Phase 1, 28 FI patients participated in anonymous on‐line focus groups, and in Phase 2, 186 people with FI, stratified by gender, race, and age completed an online survey. Key Results: Focus group participants described frequency and urgency as the most important characteristics for defining FI. Most (80%) thought staining of underwear constitutes FI, but only 33% thought gas leakage was FI. When asked how the success of treatment should be defined, 77% said by a reduction in frequency or complete cure, but less than half thought a 50% reduction in frequency was enough. When asked how much reduction would be needed, responses averaged 80%. The Phase 2 survey confirmed that frequency, urgency, and intestinal discomfort are the most important characteristics for case definition, and that success should be defined by at least a 75% decrease in frequency. A 50% reduction was an acceptable endpoint for 58% overall but only 26% for those aged ≥65. "Adequate relief" was acceptable to 78%. Conclusions and Inferences: Inclusion criteria for trials should specify a minimum frequency of FI. Most patients would require a ≥75% reduction in FI frequency to call a treatment successful but young adults and those with more severe FI would accept a ≥50% reduction as meaningful. Abstract : Current case definitions for fecal incontinence and trial endpoints were developed without patient input. Using focus groups and a national survey we identified a case definition and trial endpoint that are acceptable to most people with fecal incontinence. At least a 75% reduction in fecal incontinence episodes is preferred to a 50% reduction as the definition of treatment success.